(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
The Islamic theology (eulim alkalam ) have several names, commonly used in one meaning, but some scientists have differentiated among some names and used them in private meaning. so is this have any scientific or practical purpose? The search will discuss meanings of that names and the cause of taking that naming and when it was appeared?.